Decision support for rehabilitation hospital scheduling - Katja Schimmelpfeng; Stefan Helber; Steffen Kasper (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
We present a detailed analysis of the patient and resource scheduling problem in rehabilitation hospitals. In practice, the predominantly therapeutical treatments and activities which are prescribed for the patients are typically scheduled manually. This leads to rigid and inefficient schedules which can have negative effects on the quality of care and the patients' satisfaction. We outline the conceptual framework of a decision support system for the scheduling process that is based on formal optimization models. To this end, we first develop a large-scale monolithic optimization model. Then we derive a numerically tractable hierarchical model system in order to deal with problem instances of realistic sizes. We report numerical results with respect to solution times, model sizes and solution quality.
Keywords: C61; 330; Rehabilitationseinrichtung; Krankenhausmanagement; Scheduling-Verfahren; Management-Informationssystem; Theorie